Report on the Aplication of Polarographic Effect of Proteins in Cancer Diagnosis - Cantero, Antonio (Revista Brasileira de Cancerologia, 1950)
In this report to your society we have not presented our experimental data. We are reserving this more technical aspect for a publication in the near future, and in which due credit is given to the financial support and encouragement, that the Câncer Research Society of Montreal, has given to this research project. By means of the dropping Mercury electrode and by the pepsin, alcohol and sulphosalysilic acid, deproteinisation methods, we have determined the cystine content in various carcinomatic and non carcinomatic samples of blood serum. The maximum high of cystine wave for normal patient serum was 25 mm. and for carcinomatous serum from 35 to 46 mm. The present study, altho only explorating in nature has yielded results of such promise that it is our opinion, the inauguration of a research program on a larger scale is now in order. Polarography may become a new blood test in cancer diagnosis.